SOSIALISASI BAHAYA PLASTIK DI LINGKUNGAN SEKITAR PT.PETROKIMIA GRESIK - Indah Nur Fauziyyah (Environmental Engineering Journal of Community Dedication, 2023)
The use of plastic in people's daily lives often contributes to the increasing amount of plastic waste, causing various risks and negative impacts. The low level of public understanding of the dangers of plastic waste is the focus of this research. Efforts to overcome these problems include conducting widespread socialization to the community, providing a thorough understanding of the dangers of plastic waste and encouraging plastic waste management practices in accordance with applicable regulations. This study uses quantitative methods by applying pre-test and post-test methods on the understanding index variable. The results showed that before socialization, 26% of respondents lacked understanding of the dangers of plastic waste. However, after the awareness-raising activities, more than 60% of respondents stated that they had a better understanding of the dangers of plastic waste. The conclusion that can be drawn is that this research activity succeeded in achieving its goal of increasing the community's understanding of the dangers of plastic waste. In this way, it is hoped that the community can play an active role in creating a cleaner, healthier environment, and can avoid the negative impacts and pollution caused by plastic waste.